Uncovering the encapsulation effect of reduced graphene oxide sheets on the hydrogen storage properties of palladium nanocubes. Issue 40 (12th October 2021) - Koh, Jinseok; Choi, Eunho; Sakaki, Kouji; Kim, Daeho; Han, Seung Min; Kim, Sangtae; Cho, Eun Seon
Abstract : Pd nanocubes are constrained by rGO sheets to significantly change the hydrogen sorption behaviour, while showing a size dependence. Abstract : Decades of research on solute-induced phase transformation of metal hydride systems have shown the possibility to enhance hydrogen storage properties through novel material design such as nanoconfinement engineering. Nevertheless, the fundamentals of mechanical stress effect on confined Pd nanoparticles remain yet to be elucidated due to the difficulty in linking with hydrogen sorption thermodynamics. Here, a thermodynamic tuning of Pd nanocubes associated with hydrogen sorption as a result of encapsulation by reduced graphene oxide (rGO) layers is demonstrated. Pd nanocubes are constrained by rGO to such a degree that the chemical potential and the pressure hysteresis of the system during hydrogen sorption drastically change while showing a size dependence. A thorough thermodynamic analysis elucidates the role of constraints on hydrogen uptake and release; despite the nanoscale regime, the thermodynamic parameters (enthalpy and entropy) during phase transition considerably increase, a phenomenon not seen before in unconstrained Pd nanoparticle systems.